2012
DOI: 10.1007/s10071-012-0582-y
|View full text |Cite
|
Sign up to set email alerts
|

The psychophysics of sugar concentration discrimination and contrast evaluation in bumblebees

Abstract: The capacity to discriminate between choice options is crucial for a decision-maker to avoid unprofitable options. The physical properties of rewards are presumed to be represented on context-dependent, nonlinear cognitive scales that may systematically influence reward expectation and thus choice behavior. In this study, we investigated the discrimination performance of free-flying bumblebee workers (Bombus impatiens) in a choice between sucrose solutions with different concentrations. We conducted two-altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…In order to test whether the near-miss to Weber’s law provides a better fit to observed data than Weber’s law we individually fitted psychometric functions as Weibull sigmoid curves using the following equation [15], [23], [24]:where x is the larger and a is the smaller of the sugar concentrations of the test and standard feeders, m is the threshold, s is the slope at the threshold, π l is the lapse rate, and β is the exponent from Equation 4. In all models x and a were the independent variables, discrimination performance was the dependent variable, and m , s and π l were estimated parameters.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to test whether the near-miss to Weber’s law provides a better fit to observed data than Weber’s law we individually fitted psychometric functions as Weibull sigmoid curves using the following equation [15], [23], [24]:where x is the larger and a is the smaller of the sugar concentrations of the test and standard feeders, m is the threshold, s is the slope at the threshold, π l is the lapse rate, and β is the exponent from Equation 4. In all models x and a were the independent variables, discrimination performance was the dependent variable, and m , s and π l were estimated parameters.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…Here we analyzed the pooled data from all 23 bats. It has been demonstrated that this type of data pooling only causes an underestimation of the slope parameter, but does not affect the threshold and lapse rate [24]. The same pooling was done in the remaining analyzed studies as well, even if individual data were available, for better comparison between data sets.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A metallic identification tag is glued to the thorax (see Fig. 2) and detected by a reader placed at strategic locations (Streit et al, 2003;Sumner et al, 2007;Ohashi et al, 2010;Stelzer and Chittka, 2010;Decourtye et al, 2011;Silcox et al, 2011;Nachev et al, 2012;Katzenberger et al, 2013). We have recently adapted the technology to detect flower-naïve bumblebees exploring unrewarding flowers (Orbán and Plowright, 2013).…”
Section: Automationmentioning
confidence: 99%